2022
DOI: 10.1088/1757-899x/1247/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Experimental testing of longitudinal acceleration in urban buses

Abstract: A vehicle’s longitudinal acceleration is one the parameters that characterize a vehicle’s motion dynamics and used, among others, to assess the comfort of public bus passengers. Rapid acceleration and braking performed by urban bus drivers can be deemed by passengers as uncomfortable and dangerous in some situations, especially for standing passengers. This paper presents an analysis of a public bus’s longitudinal acceleration recorded during extreme acceleration and braking attempts. The experimental tests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Three-axis accelerometers are used to measure vehicle acceleration relative to three perpendicular coordinate axles. Examples of using three-axis accelerometers for vehicle dynamics testing can be found in [ 1 , 2 , 3 ]. Currently, there are increasing numbers of studies in which accelerometers are mounted in wheel rims [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three-axis accelerometers are used to measure vehicle acceleration relative to three perpendicular coordinate axles. Examples of using three-axis accelerometers for vehicle dynamics testing can be found in [ 1 , 2 , 3 ]. Currently, there are increasing numbers of studies in which accelerometers are mounted in wheel rims [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bus drivers often work at night, on weekends and public holidays. Based on the research presented in [33], it was found that fatigue and the need for the recuperation of the body mediate the relationship between work tension and risky driving behaviour [21,34]. The driver's fatigue is caused by many personal factors, such as stress and the need for organizational support, as well as factors related to the working environment [4,18,35].…”
Section: Introductionmentioning
confidence: 99%
“…This allows for the conclusion that any such behaviour may result in a high risk of a road accident. The correlation analysis presented in [33] allowed for the determination of indexes of a positive and significant relationship between the errors of reaction while driving a vehicle and general fatigue of the driver and the fatigue caused by driving. Fatigue results (both general and work-induced) translated into the higher rates of risky driving behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation